Optimal dietary concentrations of vitamin C and chromium for alleviating the effect of low ambient temperature on serum insulin, corticosterone, and some blood metabolites in laying hens - Şahin, Kazım; Önderci, M (Wiley-Liss, 2002)
This experiment was conducted to evaluate the effects of vitamin C (L-ascorbic acid) and chromium (chromium picolinate, CrPic) on serum insulin, corticosterone, and some metabolites in laying hens (Hy-Line) reared under a low ambient temperature (6.2degreesC). One hundred eighty laying hens (32 weeks old) were divided into six groups, with 30 hens per group. The experiment was designed in a 2 x 3 factorial arrangement using two levels of vitamin C (125 and 250 mg/kg of diet) and three levels of CrPic (200, 400, or 800 mug/kg of diet). The highest values for insulin, total protein, and albumin (P = 0.001) and the lowest values for corticosterone, glucose, triglyceride, and cholesterol (P = 0.001) were obtained when 250 mg of vitamin C was included with either 400 or 800 mug Cr per kg of diet. Interaction between vitamin C and chromium was detected for only insulin (P = 0.03). Serum activities of SGOT and SGPT were not influenced by dietary vitamin C or chromium (P > 0.45); however, serum activity of AP increased (P = 0.001). Increasing both dietary vitamin C and chromium caused an increase in serum concentrations of Ca, P, and K (P = 0.001) but a decrease in serum concentrations of Na (P = 0.001). The results of the present study suggest that dietary supplements of vitamin C and chromium alter serum hormone and metabolite status of laying hens and that supplementing a combination of vitamin C (250 mg/kg of diet) and chromium (400 or 800 mug Cr/kg of diet) can positively influence the performance of laying hens reared under low ambient temperature.
Keywords: Ascorbic-Acid; Manganese Proteinate; Cold Stress; Performance; Broilers; Heat; Responses; Glucose; Growth